ISLAM DAN DOKTRIN MILITERISME - Fatwa, Ach. Fajruddin (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2012)
Islam is a religion of peace. To reconcile Islam wi th militarism would require an adequate explanation. Although since the beginning of its pr esence, Islam has experienced a variety of physical conflict and war, It does not m ean that Islam gives excessive attention to the establishment of military force as an inhere nt part of life. Military establishment in Islam is due to respond to the many distractions, c hallenges and attacks of the opponent. Islamic military organization is not neatly arrange d entirely. Slowly but sure, military organizations become more organized, slim and effec tive. Likewise, Islamic provisions that regulate matters relating to war is a form of Islamic law which is a real response to the social development. In addition military tradit ion that developed is a real response to physical threats that affecting Muslims. Therefore, Islam intentionally have limited warfare just in the three concrete forms: the time and location of a limited war as well as strict distinction in the treatment of military civ il war.***Islam adalah agama perdamaian. Menyandingkan Islam dengan militerisme sudah tentu membutuhkan suatu penjelasan yang memadai. Walaupun sejak awal kehadirannya Islam telah mengalami beragam konflik fisik dan pep erangan bukan berarti Islam memberikan perhatian berlebihan kepada pembentukan kekuatan militer sebagai bagian inherent dari kehidupan. Pembentukan militerdalam Islam lebih dikarenakan merespon banyaknya gangguan, tantangan dan seranganlawan. Organisasi militer Islam ini tidak sepenuhnya tertata rapi. Perlahan tetapi pasti organisasi militer menjadi lebih terorganisir, ramping dan efektif. Demikian juga, k etentuan Islam yang mengatur hal-hal yang berkaitan dengan perang adalah bentuk konkret respon hukum Islam terhadap perkembangan sosial kemasyarakatan. Tradisi militerisme yang berkembang merupakan respon konkret terhadap ancaman fisik yang menimpa kaum Muslimin. Oleh sebab itu, Islam secara sengaja telah membatasi peperanga n dalam tiga bentuk konkret, yaitu waktu dan lokasi peperangan yang terbatas serta adanya distingsi tegas perlakuan sipil militer dalam peperangan.***Keywords: jihad, Â militer, perang, siyÄsah